ANALISIS KUALITAS LAYANAN PROGRAM LISTRIK PINTAR (PRABAYAR) DI PT.PLN (PERSERO) PEKANBARU - Saputra, Alfian; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The Service Quality Analysis of PT. PLN Indonesia (Persero) (A Case Study inProgram Quality Smart Electricity (Prepaid) at PT.PLN (Persero) Pekanbaru).This research aimed to describe the service quality of PT. PLN Indonesia(Persero) Pekanbaru in the program quality smart electricity (prepaid) and todetermine the factors inhibiting the program quality of smart electricity. Themethod used in this research is descriptive qualitative research in order to obtain acomprehensive overview and in-depth based on interviews with informants anddirect observation. The results showed that the services provided by PT. PLNIndonesia (Persero) Pekanbaru can be said to be good, but there is still a smallportion that is considered not optimal. Factors that hinder the Smart Electricity,namely: 1) Available tool and infrastructure; 2) Technical constraint field; 3)Perception of Public; and 4) lack of socialization.Keyword: Service Quality, PT. PLN Indonesia (Persero), Smart Electricity